2010
DOI: 10.5581/1516-8484.20110012
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of paroxysmal nocturnal hemoglobinuria in patients attended in Belém, Pará, Brazil

Abstract: Background Paroxysmal nocturnal hemoglobinuria is a hematological disease with complex physiopathology. It is genetically characterized by a somatic mutation in the PIG-A gene (phosphatidylinositol glycan anchor biosynthesis, class A), in which the best known antigens are DAF (decay accelerating factor or CD55) and MIRL (membrane inhibitor of reactive lysis or CD59). Objective To determine the frequency of paroxysmal nocturnal hemoglobinuria in patients attended at the HEMOPA foundation from November 2008 to J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A few studies have previously reported PNH case series in Brazil, mostly in single-center reports. In 2011, by Brito Jr. et al reported nine patients identified with PNH by flow cytometry in a sample of 30 suspected cases in the city of Belém, Pará [ 21 ]. At the 2019 American Society of Hematology annual meeting, Yamakawa et al presented data from 109 patients with a PNH clone treated at two centers in the city of São Paulo, SP, of which 56 had hemolytic disease [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have previously reported PNH case series in Brazil, mostly in single-center reports. In 2011, by Brito Jr. et al reported nine patients identified with PNH by flow cytometry in a sample of 30 suspected cases in the city of Belém, Pará [ 21 ]. At the 2019 American Society of Hematology annual meeting, Yamakawa et al presented data from 109 patients with a PNH clone treated at two centers in the city of São Paulo, SP, of which 56 had hemolytic disease [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…PNH can occur at any age, but it is generally diagnosed between third and fifth decades. [2][3][4][5] Patients experience intravascular hemolysis, smooth muscle dystonia, renal failure, arterial and pulmonary hypertension, recurrent infectious diseases, and an increased risk of notably dreadful thrombotic complications. [6] The diagnosis of PNH is made by means of clinical findings and laboratory tests to confirm the degree of hemolysis (haptoglobin, lactate dehydrogenase, direct Coombs test, reticulocyte count and total bilirubin and bilirubin fraction) and deficiency of anchored proteins of the complement system (CD55, CD59, and FLAER) in granulocytes (CD15, CD33, and CD24) and monocytes (CD14 and CD64) by flow cytometry, the gold standard method.…”
Section: Introductionmentioning
confidence: 99%
“…As regards sex, in Europe, PNH is more common in women, whereas in Asia it is more common in men. PNH can occur at any age, but it is generally diagnosed between third and fifth decades [2–5] . Patients experience intravascular hemolysis, smooth muscle dystonia, renal failure, arterial and pulmonary hypertension, recurrent infectious diseases, and an increased risk of notably dreadful thrombotic complications [6] …”
Section: Introductionmentioning
confidence: 99%